2015
DOI: 10.1038/cddis.2015.71
|View full text |Cite
|
Sign up to set email alerts
|

In vitro evidence for senescent multinucleated melanocytes as a source for tumor-initiating cells

Abstract: Oncogenic signaling in melanocytes results in oncogene-induced senescence (OIS), a stable cell-cycle arrest frequently characterized by a bi- or multinuclear phenotype that is considered as a barrier to cancer progression. However, the long-sustained conviction that senescence is a truly irreversible process has recently been challenged. Still, it is not known whether cells driven into OIS can progress to cancer and thereby pose a potential threat. Here, we show that prolonged expression of the melanoma oncoge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
52
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(54 citation statements)
references
References 53 publications
2
52
0
Order By: Relevance
“…It has also been suggested that these characteristics of melanoma are correlated with the presence of a subpopulation of tumor-initiating cells called cancer stem cells. Recent studies have identified a subpopulation with the same characteristics of stem cells in human cancer and fresh tumors [38,39].…”
Section: Discussionmentioning
confidence: 99%
“…It has also been suggested that these characteristics of melanoma are correlated with the presence of a subpopulation of tumor-initiating cells called cancer stem cells. Recent studies have identified a subpopulation with the same characteristics of stem cells in human cancer and fresh tumors [38,39].…”
Section: Discussionmentioning
confidence: 99%
“…These accumulating senescent cells can (iii) damage surrounding cells (Biran and Krizhanovsky, 2015) and cause (iv) cancer (Leikam et al, 2015) and (v) other agerelated diseases, such as atherosclerosis (Erusalimsky and Kurz, 2005;Fischer et al, 2013;Nishimatsu et al, 2015). Although senescent cells play an important role in (vi) tumor suppression (Tominaga, 2015), (vii) wound healing (Demaria et al, 2014) and development, (viii) periodically removing them does not produce significant side-effects .…”
Section: Discussionmentioning
confidence: 99%
“…However, accumulation of senescent cells in tissues is detrimental to the animal (Herbig et al, 2006;Jeyapalan et al, 2007) as these non-functional cells directly and indirectly damage surrounding cells (Salama et al, 2014). Examples of such damage include occupying niches required by competent cells to function , secreting transforming, inflammatory and otherwise damaging components of the SASP (Campisi and d'Adda di Fagagna, 2007;Coppé et al, , 2008, promoting tumour formation (Leikam et al, 2015;Zacarias-Fluck et al, 2015) and contributing to various age-related diseases such as atherosclerosis (Irvine et al, 2014;Wang and Bennett, 2012).…”
Section: Senescent Cells In Health and Diseasementioning
confidence: 99%
“…16, 17, 18 Regrowth from giant cells via de-polyploidization terminated by budding of the daughter cells has been observed in senescent fibroblasts 19 and in cancer cells after radiation therapy, 20, 21 chemotherapy 22, 23, 24, 25, 26 and RAS oncogene activation. 27 Polyploidy can facilitate senescence-induced replication barrier and promote tumor progression. 28 Whole-genomic doubling has been shown to accelerate cancer genomic evolution.…”
Section: Introductionmentioning
confidence: 99%